2022
DOI: 10.14719/pst.1337
|View full text |Cite
|
Sign up to set email alerts
|

In vitro growth and content of vincristine and vinblastine of Catharanthus roseus L. hairy roots in response to precursors and elicitors

Abstract: Catharanthus roseus L. is a medicinal plant that produces numerous indole terpenoid alkaloids, including vincristine and vinblastine, which are used for cancer treatment. The effect of specified precursors (L-phenylalanine, L-tyrosine) and elicitors (chitosan, methyl jasmonate) on C. roseus hairy roots (CHR) growth has been examined in order to increase the content of vincristine and vinblastine. Our results showed that CHR generated by an Agrobacterium rhizogenes strain isolated in Vietnam was capable of prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…To date, many studies have utilized chitosan as an elicitor, which has been shown to effectively enhance the biosynthesis of pharmaceutically useful compounds in both in vitro and in planta systems. In hairy root cultures, chitosan elicitation has increased the content of specialized compounds such as flavonoids, triterpenoid saponins, and terpenoid alkaloids [ 38 40 ]. However, the present study found no such stimulation – the content of saponins in hairy root tissue decreased in time, and the content of saponins released to the culture medium first increased and then decreased, showing a non-uniform pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have utilized chitosan as an elicitor, which has been shown to effectively enhance the biosynthesis of pharmaceutically useful compounds in both in vitro and in planta systems. In hairy root cultures, chitosan elicitation has increased the content of specialized compounds such as flavonoids, triterpenoid saponins, and terpenoid alkaloids [ 38 40 ]. However, the present study found no such stimulation – the content of saponins in hairy root tissue decreased in time, and the content of saponins released to the culture medium first increased and then decreased, showing a non-uniform pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hairy root cultures enable the modulation of metabolism in several pathways, as in the case of tropane and indole alkaloid biosynthesis. Despite reports that hairy roots fail to synthesize the dimeric vinblastine and vincristine molecules because their biosynthesis remains highly restricted to the leaves ( Sharma et al, 2018 ), some authors have demonstrated the accumulation of these alkaloids in hairy roots ( Hanafy et al, 2016 ; Vu et al, 2022 ).…”
Section: Plant Transformation Methods To Enhance Alkaloids Contentmentioning
confidence: 99%